Acquired Resistance of EGFR-Mutated Lung Cancer to Tyrosine Kinase Inhibitor Treatment Promotes PARP Inhibitor Sensitivity - Marcar, Lynnette (Cell Rep, 2019)
Lung cancers with oncogenic mutations in the epidermal growth factor receptor (EGFR) invariably acquire resistance to tyrosine kinase inhibitor (TKI) treatment. Vulnerabilities of EGFR TKI-resistant cancer cells that could be therapeutically exploited are incompletely understood. Here, we describe a poly (ADP-ribose) polymerase 1 (PARP-1) inhibitor-sensitive phenotype that is conferred by TKI treatment in vitro and in vivo and appears independent of any particular TKI resistance mechanism. We find that PARP-1 protects cells against cytotoxic reactive oxygen species (ROS) produced by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX). Compared to TKI-naive cells, TKI-resistant cells exhibit signs of increased RAC1 activity. PARP-1 catalytic function is required for PARylation of RAC1 at evolutionarily conserved sites in TKI-resistant cells, which restricts NOX-mediated ROS production. Our data identify a role of PARP-1 in controlling ROS levels upon EGFR TKI treatment, with potentially broad implications for therapeutic targeting of the mechanisms that govern the survival of oncogene-driven cancer cells.